Syphilis in Pregnancy: The Reality in a Public Hospital - Rafael Garcia Torres; Ana Laura Neves Mendonça; Grazielle Cezarine Montes; Jacqueline Jácome Manzan; João Ulisses Ribeiro; Marina Carvalho Paschoini (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective: The present study assessed epidemiological and obstetrical data from pregnant women with syphilis at the Hospital de Clínicas of the Universidade Federal do Triângulo Mineiro (UFTM, in the Portuguese acronym), describing this disease during pregnancy and its vertical transmission for future healthcare actions. Methods: Records from pregnant women who had been admitted to the Obstetrics Department of the Hospital de Clínicas of the UFTM and were diagnosed with syphilis between 2007 and 2016 were reviewed. A standardized form was used to collect epidemiological, obstetric data and outcomes of congenital infection. The present research has been authorized by the Ethics Committee of the institution. Results: There were 268 women diagnosed with syphilis, with an average age of 23.6 years old. The majority of the patients were from Uberaba. Inadequate prenatal care was observed in 37.9% of the pregnant women. Only 34.2% of the patients completed the treatment according to the guidelines issued by the Ministry of Health of Brazil, and 19.8% of the partners of the patients underwent adequate syphilis treatment; 37 (13.8%) couples (patients and partners) underwent correct treatment. Regarding the obstetric outcomes, 4 (1.5%) patients had a miscarriage and 8 (3.4%) had fetal losses (from the fetal loss group, 7 had no adequate treatment); 61 (25.9%) patients had premature births - this prematurity has been significantly correlated to inadequate or incomplete treatment in 49 (27.9%) patients, compared with 12 (13.0%) patients with premature births and adequate treatment (p = 0.006). The average live newborn weight was 2,840 g; 25.3% had a birth weight < 2,500 g; 74.2% had congenital syphilis, a data with heavy correlation to inadequate or incomplete prenatal care, prematurity, and low birth weight. Conclusion: Public awareness policies on adequate prenatal care, intensification of serological screening, and early treatment of syphilis are needed, considering the rise of cases diagnosed during gestation and its potentially preventable deleterious consequences related to congenital transmission.